GSM RCCB backup power fault control / Yusfaizal Amri Mohamad, Nur Shakira Ismail and Wan Nur Azianie Fazrina Wan Deris - Mohamad, Yusfaizal Amri; Ismail, Nur Shakira; Wan Deris, Wan Nur Azianie Fazrina (2013)
The GSM RCCB Backup Power Fault Control Project is designed for the purpose of controlling the home appliances power when the electricity supply trips out. During the earth fault such as lightning, the RCCB will trip and turn OFF automatically for the safety purposed. However, this condition will cause the power failure and therefore the home appliance cannot be function. This project can help homeowners to activate RCCB in their house automatically by using mobile phone although from the long distance without having to return home and turn ON RCCB manually. It also can inform the homeowners about the electricity supply trips out by sending the SMS to mobile phone. The objective of this project are to provide the backup electricity that cause by power fault by switching On another RCCB using short messaging service (SMS) and to apply communication system for RCCB backup power fault control using mobile phone. The GSM RCCB Backup Power Control operation starts when the RCCB is trip cause by earth fault. The SMS will be sent to the user through mobile phones which has set in the system to report the tripping. User need to reply the SMS by using a certain command to turn ON another backup RCCB automatically. This project used PIC18F4520 to send the data of the tripping report to the GSM and activated the RCCB.